A Comparison Survey of Multiple Access Scheme for upcoming 4G Communication (International Journal of Engineering and Computer Science, 2016)
Ever since wireless broadband communication services were introduced, its demand has been growing constantly. Over the last twenty years, wireless communications have become popular all across the world. It provides an attractive option for many private as well as administrative communication requirements due to various attributes including cost, effectiveness, and agility. The new generation mobile communication systems i.e. fourth generation (4G) are required to support multiple services in various types of environments. 4G is being developed to accommodate the quality of service and essential data rate like wireless broadband access, Multimedia Messaging Service (MMS), video chat, mobile TV. This paper throws light on numerous multiple access techniques anticipated in 4G communication systems. Among all the multiple access (MA) techniques, it is tried to demonstrate that IDMA (Interleave Division Multiple Access) technology can competently alleviate the interference among users and provision high data rates without compromising the quality of service that is required.